Bird Diversity in Smallholders Oil Palm Plantation in Riau Province - Yanto Santosa; Anxious Yoga Perdana; Sandi Sopiyandi; Yohanna Yohanna (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2018)
Within the last few decades, oil palm (Elaeis guine) has become one of the most rapid crop plantations being widely cultivated in Indonesia. Land clearing for stallholder plantation is made by people, either individually or in group. Forest clearing for planting activities may cause changes to the composition of the ecosystem. Birds have a signifcant role in the ecosystem, such as pollinators, seed spreader and pest control. It was claimed that bird richness decreases at least 60% due to changes in land cover into plantations. This claim needs to be further verifed. The objective of this study is to identify bird diversity and determine thesimilarity of the bird community in some smallholder oil palm plantations in Kuantan Singingi, Pelalawan and Siak District in Riau Province. Data collection had been conducted using transect method with length of 1 km and width of 50 m. Observations were done at 8 smallholder oil palm plantations in the morning from 6:00 to 8:30 pm and in the afternoon from 15:30 to 18:00 pm with 3 times repetition. Data in the study were analyzed by Margalef Index (Dmg), evenness (E) and community similarity (IS). This research showed that there are 22 species of birds from 15 families. The highest value of diversity and richness was in the plantation 1 while the highest evenness was in the plantation 5. The lowest diversity was in SH5 (H '= 1.79), the lowest richness was plantation 6 (Dmg = 2.50) and the lowest evenness value was in the plantation 4 (E = 0.90). The highest value of community similarity recorded between plantation 1-plantation 4 (IS = 0.92) while the lowest was seen between plantation 5-plantation 7 (IS =0.44). Similar habitat conditions a?ect the value of the bird community similarity.